2007
DOI: 10.1175/jcli4249.1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a Reconstructed Oceanic Kelvin Wave Dynamic Height Dataset for the Period 1974–2005

Abstract: Intraseasonal oceanic Kelvin waves are the dominant mode of variability in the thermocline of the equatorial Pacific. Dynamic height data from the Tropical Atmosphere Ocean (TAO) Array of buoys moored in the tropical Pacific offer a convenient grid on which to study the waves but can only be effectively applied to study basinwide wave activity since about 1988 because of insufficient data at earlier times. Kelvin wave signals are also present in sea level data from island and coastal sites from the University … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 20 publications
1
27
0
Order By: Relevance
“…1 are often observed in other periods based on a composite analysis using 16 yr of TAO data. This systematic behavior was also confirmed for an earlier record of island sea level data going back to 1974 (Roundy and Kiladis 2007).…”
Section: Introductionsupporting
confidence: 83%
See 4 more Smart Citations
“…1 are often observed in other periods based on a composite analysis using 16 yr of TAO data. This systematic behavior was also confirmed for an earlier record of island sea level data going back to 1974 (Roundy and Kiladis 2007).…”
Section: Introductionsupporting
confidence: 83%
“…They showed that the maximum Kelvin wave amplitude occurs at periods around 70 days for realistic propagating wind anomalies. Roundy and Kiladis (2006;hereafter RK06) proposed that an alternative process might be responsible for the discrepancy, which is of particular interest to the present study. They analyzed 16 yr of TOGA TAO data to describe the nature of intraseasonal Kelvin waves and their relationship to atmospheric forcing, and they frequently observed a systematic decrease in Kelvin wave phase speed over time.…”
Section: Introductionmentioning
confidence: 72%
See 3 more Smart Citations